Comparison of Clinical, Laboratory Parameters, and Outcome of COVID-19-Positive and Negative Neonates Delivered from COVID-19-Positive Mothers - Singh, Preeti; Kumar, Ankur; Mehta, Anita; Chauhan, Mudit (Journal of Pediatric Infectious Diseases, 2023)
Objective Severe acute respiratory syndrome coronavirus 2 is a highly contagious respiratory viral infection that affects all individuals, although neonates are considered to be the most susceptible populations; therefore, this study was conducted to evaluate the clinical outcome and association between coronavirus disease 2019 (COVID-19)-positive mothers and newborns.Methods This cross-sectional study was conducted at a dedicated COVID-19 tertiary care hospital in India over a period of 1 year. The pregnant mothers infected with COVID-19 virus were enrolled with their newborn baby up to the age of 28 days. COVID-19 test was done by using a rapid antigen kit and further confirmed by reverse-transcription polymerase chain reaction.Results Prevalence of COVID-19-positive newborns born of COVID-19-positive mothers is reported at 8.4%. Female:male ratio was found to be 1:1.2. Raised D-dimer (88.9%) and C-reactive protein (88.9%) were the most common findings in COVID-19-positive newborns followed by leucopenia (33.3%). Among the COVID-19 newborns, Apgar score less than or equal to 7 and respiratory distress were found in 55.6 and 33.3%, respectively. Out of 9 COVID-19-positive newborns, two (22.2%) were expired, and out of 98 COVID-19-negative newborns, 4(4.1%) were expired.Conclusion This study revealed that severity of maternal symptoms is related to mortality of newborns. About 22.2% COVID-19-positive newborns expired, whereas 4.1% of COVID-19-negative newborns expired so risk of mortality increased among COVID-19-positive neonates as compared with negative ones. However, this study was conducted on a small sample size and further research with larger populations is needed to validate these findings.
Keywords: COVID-19; APGAR score; respiratory distress; SARS-CoV-2